Population pharmacokinetic analysis of remimazolam after continuous infusion for sedation in critically ill patients - Chen, Jingchun; Wang, Xipei; Chen, Dong; Liu, Xiaolong; Peng, Kaiyi; Tang, Ruizheng; Hu, Linhui; Wang, Yirong; Bai, Yunpeng; Chang, Lin; Chen, Chunbo (Frontiers in Pharmacology, 2025)
IntroductionThe aim of the present prospective study was to model the population pharmacokinetics of remimazolam after continuous infusion in critically ill patients, and to provide a guide for remimazolam administration based on simulations that were conducted.Patients and methodsA total of 32 critically ill patients were enrolled in this study, with 236 plasma concentration data ultimately included for modeling. Plasma concentrations of remimazolam were quantified by a validated high-performance liquid chromatography-tandem mass spectrometry method, and the data were analyzed using non-linear mixed effect modeling. Concentration-time curves of remimazolam at different induction and maintenance doses were simulated and context-sensitive decrement times (CSDTs) were calculated using Monte Carlo simulations.ResultsA two-compartment model appropriately described the concentration-time profile of remimazolam in critically ill patients. The elimination clearance, volume of the central compartment, volume of the peripheral compartment, and peripheral compartmental clearance were estimated to be 58.2 L/h (95% CI, 47.8–72.3 L/h), 25.5 L (95% CI, 16.8–33.3 L), 34.5 L (95% CI, 26.0–58.8 L) and 21.9 L/h (95% CI, 12.2–34.6 L/h), respectively. No covariates significantly influenced the pharmacokinetic parameters of remimazolam. Internal validation proved the reliable predictive performance of the model. The CSDTs of remimazolam (10%–90%) was independent of the infusion time.ConclusionRemimazolam showed a predictable pharmacokinetic profile and was demonstrated to be suitable for long-term sedation in the intensive care unit, with dose adjustments only required dependent on the degree of the sedative effect.